INTEGRATION OF LEGAL AND ECONOMIC PERSPECTIVES IN BRANDING STRATEGY: A LITERATURE REVIEW ON FAIR BUSINESS COMPETITION, CONSUMER PROTECTION, AND TRADEMARK PROTECTION - Gunawan Widjaja (CV. Adiba Aisha Amira, 2026)
The integration of legal and economic perspectives in branding strategies is important in maintaining a balance between corporate competitiveness, fair business competition, consumer protection, and trademark protection. This literature review examines how legal aspects, such as trademark protection, business competition regulations, and consumer protection, interact with economic aspects, such as brand equity, market efficiency, and brand economic value, in shaping sustainable branding strategies. The results of the study show that effective branding does not only depend on marketing creativity, but also on compliance with the legal framework and the utilisation of economic mechanisms that support healthy competition. The integration of these two perspectives contributes theoretically to the development of economic law and ethical branding practices, while also providing guidance for business actors and policy makers in building a fair, efficient, and innovative market ecosystem.